1989
DOI: 10.1143/jjap.28.1041
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of SiO2/Si Interface Properties Utilising Fluorine Ion Implantation and Drive-in Diffusion

Abstract: Thermal drive-in diffusion of ion-implanted F atoms has been employed to fluorinate SiO2/Si interfaces and thereby improve their electrical properties. The interface state density can be lowered with little fixed charge generation. Correspondingly, pn-junction surface leakage current decreases. Furthermore, the interfaces can be hardened against hot-electrons due to Fowler-Nordheim current injection and avalanche current at the junction surface. As a result, a fluorinated MOSFET shows higher hot-carrier immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Figure 1 illustrates three serious technological issues with the CMOS image sensor fabrication process. [4][5][6][7] The first issue is metallicimpurity contamination during device fabrication. 5,6,8,9) The second issue is the out-diffusion of oxygen impurity to the epitaxial layer from the Czochralski (CZ)-grown silicon wafer substrate during device fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates three serious technological issues with the CMOS image sensor fabrication process. [4][5][6][7] The first issue is metallicimpurity contamination during device fabrication. 5,6,8,9) The second issue is the out-diffusion of oxygen impurity to the epitaxial layer from the Czochralski (CZ)-grown silicon wafer substrate during device fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…A low density of carrier traps in SiO2 films was achieved using ultra-dry oxid.i zLnq atmospher" . 4 ) F and Cl in SiO2 suppressed the generation of interface states.5r 6) we already reported that damage-free photo-excited cleaning with CIZ improved the break-down field of SiO2 and. surface recombination velocity at a Si-etch depth of more than 30 nm.…”
Section: Introductionmentioning
confidence: 82%
“…14 Because of the stronger bonding energy of the Si-F bond ͑5.73 eV͒, F bonds favorably to Si compared to the Si-H bond ͑3.18 eV͒ 14 or Si-O bond. [21][22][23][24][25][26] In our test structure, FSO was deposited on TEOS oxide, which is placed on the wafer surface atop the device passivation. This way excessive fluorine causes a negative charge buildup in the bulk gate oxide.…”
Section: Discussionmentioning
confidence: 99%